Do Patients with Acute Low Back Pain in Emergency Departments Have More Severe Symptoms than Those in General Practice? ASystematic Review with Meta-Analysis. Issue 4 (4th September 2021) - Oliveira, Crystian B; Hamilton, Melanie; Traeger, Adrian; Buchbinder, Rachelle; Richards, Bethan; Rogan, Eileen; Maher, Chris G; Machado, Gustavo C
Abstract: Introduction: There is a common belief that patients presenting to emergency departments have more severe pain levels and functional limitations than those who are seen in general practice. The aim of this systematic review was to compare pain and disability levels of patients with acute low back pain presenting to general practice vs those presenting to emergency departments. Methods: Electronic searches were conducted in MEDLINE, EMBASE, and CINAHL from database inception to February 2019. Observational studies including patients with acute non-specific low back pain presenting to emergency departments and/or general practice were eligible. Pain and/or disability scores expressed on a 0–100 scale were the primary outcomes. Risk of bias was evaluated with a validated tool for observational studies, and the overall quality of evidence was assessed with Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Meta-analysis with random effects and meta-regression were used to test for differences between the two settings. Results: We included 12 records reporting results for 10 unique studies with a total of 6, 999 participants from general practice (n = 6) and emergency departments (n = 4). There was low-quality evidence (downgraded for indirectness and inconsistency) that patients presenting to emergency departments had higher pain scores than those in general practice, with a mean difference of 17.3 points (95% confidence interval: 8.8 to 25.9 on a 0–100 scale). Similarly, there was low-quality evidence (downgraded for indirectness and inconsistency) that patients presenting to emergency departments had higher disability scores than those in general practice (mean difference: 21.7; 95% confidence interval: 4.6 to 38.7 on a 0–100 scale). Conclusion: Patients with acute non-specific low back pain presenting to emergency departments may report higher levels of pain and disability than those seen in general practice.